Unburned magnesia-alumina spinel brick for RH refining furnace immersion tube and preparation method thereof

By regulating the ratio of magnesium sand and magnesium aluminum spinel and adding titanium dioxide powder and boron oxide powder to promote the reaction to form titanate, the resistance of magnesium aluminum spinel bricks in high temperature and slag erosion environment is solved, and the performance problem of magnesium aluminum spinel bricks is achieved. The high efficiency of high temperature resistance, wear resistance and slag resistance of RH refining furnace impregnation tube bricks.

CN118812241BActive Publication Date: 2024-12-13BEIJING LIRR HIGH-TEMPERATURE MATERIALS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411307760.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The magnesium-aluminum spinel bricks used in the impregnation tube of the RH refining furnace are difficult to have excellent corrosion resistance, high temperature and wear resistance in high temperature and slag erosion environments.

Method used

By regulating the ratio of magnesium sand and magnesium aluminum spinel, and adding titanium dioxide powder and boron oxide powder, the reaction between magnesium oxide and alumina is promoted to form magnesium titanate and aluminum titanate, improving the bonding of the material, and at high temperatures MgAlON is formed to enhance the slag resistance and thermal shock stability of the brick.

Benefits of technology

Magnesium aluminum spinel bricks have good high temperature resistance, wear resistance and slag resistance at high temperatures, extending service life and reducing production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an unburned magnesia-alumina spinel brick for an RH refining furnace dip tube and a preparation method thereof. The raw materials for preparing the unburned magnesia-alumina spinel brick for an RH refining furnace dip tube include the following components in percentage by mass: 3% to 37% of fused magnesia sand, 34.5% to 79% of large-crystal fused magnesia sand, 8% to 12% of magnesia-alumina spinel, 3% to 12% of silicon carbide, 1.5% to 5% of metal aluminum powder, 0.2% to 3% of titanium dioxide powder and 0.2% to 2.5% of boron oxide powder, and 1% to 5% of an external binder. The unburned magnesia-alumina spinel brick for an RH refining furnace dip tube has excellent corrosion resistance, high temperature resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to an unburned magnesia-alumina spinel brick for an RH refining furnace immersion tube and a preparation method thereof. Background Art

[0002] At present, the RH vacuum refining furnace is the main off-furnace refining process, and the technology has been rapidly developed. The RH refining furnace immersion tube is a key component for the circulation of molten steel in the RH vacuum refining device, and is mainly composed of an ascending tube and a downcomer. They are connected to the vacuum tank and the ladle respectively, and a pressure difference is formed by blowing in argon gas, so that the molten steel circulates between the vacuum tank and the ladle, thereby realizing the refining processes of the molten steel such as degassing, decarbonization, and desulfurization. The inside and outside of the immersion tube are covered with refractory materials to withstand high temperatures and erosion of molten steel. Commonly used refractory materials for the RH refining furnace immersion tube include magnesia-chrome bricks, chrome corundum castables, etc. These materials have high temperature stability, corrosion resistance and good thermal shock stability. However, materials containing Cr2O3 will produce Cr during high-temperature use. 6+ ,Cr 6+ It is highly carcinogenic and easily soluble in water, causing serious environmental problems. With the development of off-furnace refining technology and the continuous improvement of environmental protection requirements, RH needs to use high-performance and environmentally friendly materials to replace magnesia-chrome bricks.

[0003] Magnesium-aluminum spinel bricks have excellent wear resistance and anti-scouring ability, and are more environmentally friendly, and can be used for RH refining furnace dip tubes. The Chinese patent document with publication number CN112047746A discloses an unfired magnesium-aluminum spinel brick for RH dip tubes and its preparation method. The unfired magnesium-aluminum spinel brick is obtained by adding composite additives and baking the mixed rolling blank. It has the characteristics of high thermal shock stability, long service life, low production cost, and high product cost performance. It can replace magnesium-chrome bricks to produce RH dip tubes. Since the RH refining furnace dip tube is subjected to the scouring of molten steel circulation in the working state, and its working environment is vacuum, the slag erosion will be more serious in the vacuum state. Therefore, compared with the lining of the refining furnace, the refractory material used for the dip tube needs to have better erosion resistance, high temperature resistance and wear resistance. For magnesium-aluminum spinel bricks, the ratio of magnesium oxide and aluminum oxide contained in magnesium-aluminum spinel can be adjusted within a certain range. Magnesium oxide has high refractoriness, so it has good high temperature resistance, but low Mohs hardness and poor wear resistance; aluminum oxide has higher Mohs hardness than magnesium oxide and good wear resistance, but it cannot withstand slag because aluminum can react with calcium oxide and silicon oxide in the slag. Therefore, how to regulate magnesium aluminum spinel bricks to have excellent corrosion resistance, high temperature resistance and wear resistance is a problem that needs to be solved at present. Summary of the invention

[0004] The technical problem solved by the present invention is to provide an unburned magnesia-alumina spinel brick for an RH refining furnace immersion tube and a preparation method thereof, which has excellent corrosion resistance, high temperature resistance and wear resistance.

[0005] In order to solve the above problems, one aspect of the present invention provides an unburned magnesia-alumina spinel brick for an RH refining furnace immersion tube, wherein the raw materials for preparing the brick include the following components in mass percentage:

[0006] Fused magnesia 3%~37%, large crystal fused magnesia 34.5~79%, magnesia alumina spinel 8%~12%, silicon carbide 3%~12%, metallic aluminum powder 1.5%~5%, titanium dioxide powder 0.2%~3% and boron oxide powder 0.2%~2.5%, plus a binder 1%~5%.

[0007] Preferably, the raw materials for its preparation include the following components in percentage by mass:

[0008] Fused magnesia 8%~35%, large crystal fused magnesia 39%~71%, magnesia alumina spinel 8%~12%, silicon carbide 5%~10%, metallic aluminum powder 1.5%~4.5%, titanium dioxide powder 0.5~2.5% and boron oxide powder 0.3%~1.8%, plus a binder 1%~5%.

[0009] Preferably, the raw materials for its preparation include the following components in percentage by mass:

[0010] Fused magnesia 19%~27%, large crystal fused magnesia 48.3~60.7%, magnesia alumina spinel 8%~11%, silicon carbide 7%~8%, metallic aluminum powder 2%~4.5%, titanium dioxide powder 0.5~2.2% and boron oxide powder 0.5%~1.5%, plus a binder 1%~5%.

[0011] Preferably, in the magnesium-aluminum spinel, the MgO content is 25wt%~45wt%, and the Al2O3 content is 55wt%~75wt%.

[0012] Preferably, the mass ratio of the total mass of fused magnesia and large-crystal fused magnesia to magnesium-aluminum spinel is 7.4-10:1.

[0013] Preferably, the mass ratio of the metallic aluminum powder, the titanium dioxide powder and the boron oxide powder is 1.5-8.5:0.8-1.7:1.

[0014] Preferably, in the fused magnesia, MgO>97.2wt%, SiO2<0.8wt%, Fe2O3<0.6wt%, Al2O3<0.15wt%, CaO<1.5wt%, and ignition loss<0.1wt%;

[0015] In large crystal fused magnesia, MgO>97.5wt%, SiO2<0.8wt%, Fe2O3<0.6wt%, Al2O3<0.15wt%, CaO<1.5wt%, ignition loss<0.1wt%;

[0016] In magnesium-aluminum spinel, MgO>32.5wt%, Al2O3>65wt%, Fe2O3<1wt%, SiO2<0.15wt%, CaO<0.5wt%, ignition loss<3.5wt%, bulk density of magnesium-aluminum spinel>3.4g / cm 3 ;

[0017] In silicon carbide, SiC>9wt7%, Fe2O3<1wt%.

[0018] Preferably, the fused magnesia includes fused magnesia particles with a particle size of >3mm and ≤5mm, fused magnesia particles with a particle size of >1mm and ≤3mm, and fused magnesia particles with a particle size of >0mm and ≤1mm; the mass ratio of the fused magnesia particles with a particle size of >3mm and ≤5mm, the fused magnesia particles with a particle size of >1mm and ≤3mm, and the fused magnesia particles with a particle size of >0mm and ≤1mm is 1:1~5:1~4;

[0019] Large crystalline fused magnesia includes large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, and large crystalline fused magnesia fine powder with a particle size of 200 mesh; the mass ratio of large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, and large crystalline fused magnesia fine powder with a particle size of 200 mesh is 1:1~2.5:1~3.

[0020] Preferably, the particle size of the magnesium aluminum spinel is 200 mesh;

[0021] The particle size of silicon carbide is 200 mesh;

[0022] The particle size of the aluminum powder is 200 mesh;

[0023] The particle size of titanium dioxide powder is 200 mesh;

[0024] The particle size of the boron oxide powder is 200 mesh.

[0025] Another aspect of the present invention provides a method for preparing the above-mentioned unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube, comprising the following steps:

[0026] Fused magnesia, large crystal fused magnesia, magnesia-alumina spinel, silicon carbide, metal aluminum powder, titanium dioxide powder and boron oxide powder are mixed, a binder is added and mixed, and the mixed material is molded to obtain the unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The unburned magnesium-aluminum spinel brick for the RH refining furnace impregnation tube of the present invention, firstly, regulates the ratio of magnesium sand and magnesium-aluminum spinel, so that at high temperature, the ratio of magnesium oxide and aluminum oxide effectively combined as a whole in the brick is regulated to make the magnesium-aluminum spinel brick have good high temperature resistance, wear resistance and slag resistance at the same time. Secondly, titanium dioxide powder is added, and titanium dioxide can be used as a promoter for the reaction of magnesium oxide with aluminum oxide in magnesium-aluminum spinel, because titanium dioxide can form magnesium titanate with magnesium oxide, and magnesium titanate and aluminum oxide can generate magnesium-aluminum spinel. Similarly, titanium dioxide can also form aluminum titanate with aluminum oxide, and aluminum titanate and magnesium oxide generate magnesium-aluminum spinel. The reaction rate of titanium dioxide with magnesium oxide or aluminum oxide is greater than the direct reaction of magnesium oxide and aluminum oxide. Therefore, the addition of titanium dioxide can promote the reaction of magnesium oxide in magnesium sand entering the magnesium-aluminum spinel lattice. Thirdly, the present invention is an unfired brick, which is not calcined before use. Therefore, it is difficult to sinter during use. The present invention further introduces boron oxide, which can form a liquid phase at a high temperature in the use environment, and the presence of the liquid phase can promote the formation of magnesium titanate and aluminum titanate. In addition, the liquid phase condition can promote the formation of a small amount of MgAlON by metal aluminum, magnesium oxide, and aluminum oxide, thereby improving the bonding of the material; more importantly, boron oxide can also react with titanium dioxide and metal aluminum to generate titanium boride and aluminum oxide, and free aluminum oxide can be used to transfer or transport aluminum oxide during the formation of magnesium aluminum spinel, thereby promoting the formation of magnesium aluminum spinel, while titanium boride is wrapped on the surface of the system to protect the system, and to a certain extent, it prevents the reaction of aluminum oxide in the system with calcium oxide in the slag. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] One aspect of an embodiment of the present invention provides an unburned magnesia-alumina spinel brick for an RH refining furnace immersion tube, wherein the raw materials for preparing the unburned magnesia-alumina spinel brick include the following components in percentage by mass:

[0031] Fused magnesia 3%~37%, large crystal fused magnesia 34.5~79%, magnesia alumina spinel 8%~12%, silicon carbide 3%~12%, metallic aluminum powder 1.5%~5%, titanium dioxide powder 0.2%~3% and boron oxide powder 0.2%~2.5%, plus a binder 1%~5%.

[0032] In magnesia-alumina spinel bricks, the higher the magnesium oxide content, the better the high temperature resistance, but the lower the wear resistance; aluminum oxide has good wear resistance, but poor slag resistance. The ratio of magnesium oxide to aluminum oxide affects its corrosion resistance, high temperature resistance and wear resistance. However, the above properties are not directly determined by the magnesium oxide and aluminum oxide content in the raw materials for its preparation, because not all magnesia sand in the raw materials can be effectively combined and sintered with magnesia-alumina spinel to form a whole. Only the magnesium oxide and aluminum oxide that form a whole can directly determine the performance of the brick. In magnesia-alumina spinel, the ratio of magnesium oxide to aluminum oxide is not a fixed value, but an adjustable range value. Therefore, when magnesia-alumina spinel and magnesia sand are at high temperature, the magnesium oxide in the magnesia sand can enter the crystal lattice of magnesia-alumina spinel and further form spinel with the aluminum oxide therein. Compared with magnesia sand alone, the formation of spinel can ensure a stronger combination between magnesium oxide and magnesia-alumina spinel.

[0033] The unburned magnesium-aluminum spinel brick for the RH refining furnace impregnation tube of the embodiment of the present invention, firstly, regulates the ratio of magnesium sand and magnesium-aluminum spinel, so that at high temperature, the ratio of magnesium oxide and aluminum oxide effectively combined as a whole in the brick is regulated to make the magnesium-aluminum spinel brick have good high temperature resistance, wear resistance and slag resistance at the same time. Secondly, titanium dioxide powder is added, and titanium dioxide can be used as a promoter for the reaction of magnesium oxide with aluminum oxide in magnesium-aluminum spinel, because titanium dioxide can form magnesium titanate with magnesium oxide, and magnesium titanate and aluminum oxide can generate magnesium-aluminum spinel. Similarly, titanium dioxide can also form aluminum titanate with aluminum oxide, and aluminum titanate and magnesium oxide generate magnesium-aluminum spinel. The reaction rate of titanium dioxide with magnesium oxide or aluminum oxide is greater than the direct reaction of magnesium oxide and aluminum oxide. Therefore, the addition of titanium dioxide can promote the reaction of magnesium oxide in magnesium sand entering the magnesium-aluminum spinel lattice. Thirdly, the present invention is an unfired brick, which is not calcined before use. Therefore, it is difficult to sinter during use. The present invention further introduces boron oxide, which can form a liquid phase at a high temperature in the use environment, and the presence of the liquid phase can promote the formation of magnesium titanate and aluminum titanate. In addition, the liquid phase condition can promote the formation of a small amount of MgAlON by metal aluminum, magnesium oxide, and aluminum oxide, thereby improving the bonding of the material; more importantly, boron oxide can also react with titanium dioxide and metal aluminum to generate titanium boride and aluminum oxide, and free aluminum oxide can be used to transfer or transport aluminum oxide during the formation of magnesium aluminum spinel, thereby promoting the formation of magnesium aluminum spinel, while titanium boride is wrapped on the surface of the system to protect the system, and to a certain extent, it prevents the reaction of aluminum oxide in the system with calcium oxide in the slag.

[0034] Preferably, the raw materials for its preparation include the following components in percentage by mass:

[0035] Fused magnesia 8%~35%, large crystal fused magnesia 39%~71%, magnesia alumina spinel 8%~12%, silicon carbide 5%~10%, metal aluminum powder 1.5%~4.5%, titanium dioxide powder 0.5~2.5% and boron oxide powder 0.3%~1.8%, and an additional binder 1%~5%. Experimental trials have found that the above mass ratio range can make the reactions in the unfired magnesia alumina spinel brick more appropriate, and the brick has better high temperature resistance, wear resistance and slag resistance.

[0036] Preferably, the raw materials for its preparation include the following components in percentage by mass:

[0037] Fused magnesia 19%~27%, large crystal fused magnesia 48.3~60.7%, magnesia alumina spinel 8%~11%, silicon carbide 7%~8%, metal aluminum powder 2%~4.5%, titanium dioxide powder 0.5~2.2% and boron oxide powder 0.5%~1.5%, and an additional binder 1%~5%. Experimental trials have found that the above mass ratio range can make the reactions in the unfired magnesia alumina spinel brick more appropriate, and the high temperature resistance, wear resistance and slag resistance of the brick are further improved.

[0038] Different contents of magnesium oxide and aluminum oxide in magnesium aluminate spinel result in different contents of magnesium oxide and aluminum oxide effectively combined as a whole in the final brick, thereby affecting the comprehensive performance of high temperature resistance, wear resistance and slag resistance of the brick. Preferably, the magnesium aluminate spinel has a MgO content of 25wt% to 45wt% and an Al2O3 content of 55wt% to 75wt%. Further preferably, the magnesium aluminate spinel has a MgO content of 30wt% to 35wt% and an Al2O3 content of 65wt% to 70wt%.

[0039] Fused magnesia and large crystalline fused magnesia are the sources of magnesium oxide, and the ratio of the two to magnesia-alumina spinel affects the comprehensive performance of high temperature resistance, wear resistance and slag resistance of magnesia-alumina spinel bricks. Preferably, the total mass ratio of fused magnesia and large crystalline fused magnesia to magnesia-alumina spinel is 7.4-10:1.

[0040] Preferably, metal aluminum powder, titanium dioxide powder and boron oxide powder can generate titanium boride and aluminum oxide in a certain ratio. In addition, titanium dioxide also serves as a medium for the reaction of magnesium oxide and aluminum oxide, and boron oxide is needed to promote their reaction and promote the formation of MgAlON. Therefore, the ratio of the three needs to be further regulated. Experimental attempts have found that preferably, the mass ratio of metal aluminum powder, titanium dioxide powder and boron oxide powder is 1.5~8.5:0.8~1.7:1. Within this ratio range, the comprehensive performance of high temperature resistance, wear resistance and slag resistance of magnesium-aluminum spinel bricks can be better.

[0041] Compared with fused magnesia, large crystal fused magnesia has higher purity and larger volume density. The mixed use of the two can reduce costs on the one hand, and on the other hand, it can produce a certain density gradient to relieve the stress caused by temperature changes and improve the thermal shock stability to a certain extent.

[0042] Preferably, in the fused magnesia, MgO>97.2wt%, SiO2<0.8wt%, Fe2O3<0.6wt%, Al2O3<0.15wt%, CaO<1.5wt%, and ignition loss<0.1wt%;

[0043] In large crystal fused magnesia, MgO>97.5wt%, SiO2<0.8wt%, Fe2O3<0.6wt%, Al2O3<0.15wt%, CaO<1.5wt%, ignition loss<0.1wt%;

[0044] In magnesium-aluminum spinel, MgO>32.5wt%, Al2O3>65wt%, Fe2O3<1wt%, SiO2<0.15wt%, CaO<0.5wt%, ignition loss<3.5wt%, bulk density of magnesium-aluminum spinel>3.4g / cm 3 ;

[0045] In silicon carbide, SiC>9wt7%, Fe2O3<1wt%.

[0046] Preferably, the fused magnesia includes fused magnesia particles with a particle size of >3mm and ≤5mm, fused magnesia particles with a particle size of >1mm and ≤3mm, and fused magnesia particles with a particle size of >0mm and ≤1mm; the mass ratio of the fused magnesia particles with a particle size of >3mm and ≤5mm, the fused magnesia particles with a particle size of >1mm and ≤3mm, and the fused magnesia particles with a particle size of >0mm and ≤1mm is 1:1~5:1~4;

[0047] Large crystalline fused magnesia includes large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, and large crystalline fused magnesia fine powder with a particle size of 200 mesh; the mass ratio of large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, and large crystalline fused magnesia fine powder with a particle size of 200 mesh is 1:1~2.5:1~3.

[0048] Preferably, the particle size of the magnesium aluminum spinel is 200 mesh;

[0049] The particle size of silicon carbide is 200 mesh;

[0050] The particle size of the aluminum powder is 200 mesh;

[0051] The particle size of titanium dioxide powder is 200 mesh;

[0052] The particle size of the boron oxide powder is 200 mesh.

[0053] Another aspect of the present invention provides a method for preparing the above-mentioned unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube, comprising the following steps:

[0054] Fused magnesia, large crystal fused magnesia, magnesia-alumina spinel, silicon carbide, metal aluminum powder, titanium dioxide powder and boron oxide powder are mixed, a binder is added and mixed, and the mixed material is molded to obtain the unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube.

[0055] Example 1

[0056] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0057] The fused magnesia includes 3% fused magnesia particles with a particle size of >3mm and ≤5mm, 14% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 25% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 28% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 12% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 3% silicon carbide with a particle size of 200 mesh, 4.5% metal aluminum powder with a particle size of 200 mesh, 0.2% titanium dioxide powder with a particle size of 200 mesh, and 0.3% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 30wt%, and the Al2O3 content is 70wt%.

[0058] Example 2

[0059] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0060] The fused magnesia includes 4% fused magnesia particles with a particle size of >3mm and ≤5mm, 10% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 28% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 28% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 11.5% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 3% silicon carbide with a particle size of 200 mesh, 5% metal aluminum powder with a particle size of 200 mesh, 0.3% titanium dioxide powder with a particle size of 200 mesh, and 0.2% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 35wt%, and the Al2O3 content is 65wt%.

[0061] Example 3

[0062] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0063] The fused magnesia includes 2% fused magnesia particles with a particle size of >3mm and ≤5mm, 2% fused magnesia particles with a particle size of >1mm and ≤3mm, 4% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 22% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 28% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 11% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 5% silicon carbide with a particle size of 200 mesh, 2.7% metal aluminum powder with a particle size of 200 mesh, 1.5% titanium dioxide powder with a particle size of 200 mesh, and 1.8% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0064] Example 4

[0065] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0066] The fused magnesia includes 4% fused magnesia particles with a particle size of >3mm and ≤5mm, 4% fused magnesia particles with a particle size of >1mm and ≤3mm, 5% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 22% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 22% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 13.7% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 6% silicon carbide with a particle size of 200 mesh, 2.5% metal aluminum powder with a particle size of 200 mesh, 0.5% titanium dioxide powder with a particle size of 200 mesh, and 0.3% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0067] Example 5

[0068] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0069] The fused magnesia includes 5% fused magnesia particles with a particle size of >3mm and ≤5mm, 9% fused magnesia particles with a particle size of >1mm and ≤3mm, 5% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 17% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 22% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 11.7% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 8% magnesia-alumina spinel with a particle size of 200 mesh, 8% silicon carbide with a particle size of 200 mesh, 3% metal aluminum powder with a particle size of 200 mesh, 0.8% titanium dioxide powder with a particle size of 200 mesh, and 0.5% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0070] Example 6

[0071] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0072] The fused magnesia includes 5% fused magnesia particles with a particle size of >3mm and ≤5mm, 9% fused magnesia particles with a particle size of >1mm and ≤3mm, 9% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 17% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 17% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 11.5% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 9% magnesia-alumina spinel with a particle size of 200 mesh, 7% silicon carbide with a particle size of 200 mesh, 3.5% metal aluminum powder with a particle size of 200 mesh, 1% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0073] Example 7

[0074] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0075] The fused magnesia includes 4% fused magnesia particles with a particle size of >3mm and ≤5mm, 14% fused magnesia particles with a particle size of >1mm and ≤3mm, 9% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 12% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 16% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 10.3% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 8% silicon carbide with a particle size of 200 mesh, 4% metal aluminum powder with a particle size of 200 mesh, 1.2% titanium dioxide powder with a particle size of 200 mesh, and 1.5% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0076] Example 8

[0077] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0078] The fused magnesia includes 4% fused magnesia particles with a particle size of >3mm and ≤5mm, 13% fused magnesia particles with a particle size of >1mm and ≤3mm, 13% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 12% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 13% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 8% silicon carbide with a particle size of 200 mesh, 4.5% metal aluminum powder with a particle size of 200 mesh, 1.5% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0079] Example 9

[0080] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0081] The fused magnesia includes 4% fused magnesia particles with a particle size of >3mm and ≤5mm, 18% fused magnesia particles with a particle size of >1mm and ≤3mm, 13% fused magnesia particles with a particle size of >0mm and ≤1mm, 8% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 9% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 12% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 10% silicon carbide with a particle size of 200 mesh, 4% metal aluminum powder with a particle size of 200 mesh, 1% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 35wt%, and the Al2O3 content is 65wt%.

[0082] Example 10

[0083] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube described in this embodiment comprises the following components in percentage by mass:

[0084] The fused magnesia includes 4% fused magnesia particles with a particle size of >3mm and ≤5mm, 18% fused magnesia particles with a particle size of >1mm and ≤3mm, 15% fused magnesia particles with a particle size of >0mm and ≤1mm, 8% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 8% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 8% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 10.5% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 10% magnesia-alumina spinel with a particle size of 200 mesh, 12% silicon carbide with a particle size of 200 mesh, 2% metal aluminum powder with a particle size of 200 mesh, 2% titanium dioxide powder with a particle size of 200 mesh, and 2.5% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 30wt%, and the Al2O3 content is 70wt%.

[0085] Embodiment 11

[0086] The unburned magnesia-alumina spinel bricks used for the RH refining furnace immersion tube in this embodiment are prepared by using the same raw materials as those in Example 6, except that the MgO content in the magnesia-alumina spinel is 30wt%, and the Al2O3 content is 70wt%.

[0087] Example 12

[0088] The unburned magnesia-alumina spinel bricks used for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the MgO content in the magnesia-alumina spinel is 35wt%, and the Al2O3 content is 65wt%.

[0089] Example 13

[0090] The unburned magnesia-alumina spinel bricks used for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the MgO content in the magnesia-alumina spinel is 25wt%, and the Al2O3 content is 75wt%.

[0091] Embodiment 14

[0092] The unburned magnesia-alumina spinel bricks used for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the MgO content in the magnesia-alumina spinel is 45wt%, and the Al2O3 content is 55wt%.

[0093] Embodiment 15

[0094] The unburned magnesia-alumina spinel bricks used for the RH refining furnace immersion tube in this embodiment are prepared by using the same raw materials as those in Example 6, except that the MgO content in the magnesia-alumina spinel is 20wt%, and the Al2O3 content is 80wt%.

[0095] Example 16

[0096] The unburned magnesia-alumina spinel bricks used for the RH refining furnace immersion tube in this embodiment are prepared by using the same raw materials as those in Example 6, except that the MgO content in the magnesia-alumina spinel is 50wt%, and the Al2O3 content is 50wt%.

[0097] Embodiment 17

[0098] The unburned magnesia-alumina spinel bricks for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the mass ratio of the total mass of fused magnesia and large-crystal fused magnesia to magnesia-alumina spinel is 7.4:1.

[0099] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube of this embodiment is prepared from raw materials including the following components in percentage by mass:

[0100] The fused magnesia includes 5% fused magnesia particles with a particle size of >3mm and ≤5mm, 9% fused magnesia particles with a particle size of >1mm and ≤3mm, 9% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 17% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 17% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 11% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 10.5% magnesia-alumina spinel with a particle size of 200 mesh, 6% silicon carbide with a particle size of 200 mesh, 3.5% metal aluminum powder with a particle size of 200 mesh, 1% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0101] Embodiment 18

[0102] The unburned magnesia-alumina spinel bricks for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the mass ratio of the total mass of fused magnesia and large-crystal fused magnesia to magnesia-alumina spinel is 10:1.

[0103] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube of this embodiment is prepared from raw materials including the following components in percentage by mass:

[0104] The fused magnesia includes 5% fused magnesia particles with a particle size of >3mm and ≤5mm, 9% fused magnesia particles with a particle size of >1mm and ≤3mm, 9% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large-crystal fused magnesia particles with a particle size of >3mm and ≤5mm, 17% large-crystal fused magnesia particles with a particle size of >1mm and ≤3mm, 17% large-crystal fused magnesia particles with a particle size of >0mm and ≤1mm, 13% large-crystal fused magnesia fine powder with a particle size of 200 mesh, 8% magnesia-alumina spinel with a particle size of 200 mesh, 6.5% silicon carbide with a particle size of 200 mesh, 3.5% metal aluminum powder with a particle size of 200 mesh, 1% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0105] Embodiment 19

[0106] The unburned magnesia-alumina spinel bricks for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the mass ratio of the total mass of fused magnesia and large-crystal fused magnesia to magnesia-alumina spinel is 6:1.

[0107] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube of this embodiment is prepared from raw materials including the following components in percentage by mass:

[0108] The fused magnesia includes 5% fused magnesia particles with a particle size of >3mm and ≤5mm, 9% fused magnesia particles with a particle size of >1mm and ≤3mm, 9% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 17% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 15% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 11% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 12.5% ​​magnesia-alumina spinel with a particle size of 200 mesh, 6% silicon carbide with a particle size of 200 mesh, 3.5% metal aluminum powder with a particle size of 200 mesh, 1% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0109] Embodiment 20

[0110] The unburned magnesia-alumina spinel bricks for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, except that the mass ratio of the total mass of fused magnesia and large-crystal fused magnesia to magnesia-alumina spinel is 12.6:1.

[0111] The unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube of this embodiment is prepared from raw materials including the following components in percentage by mass:

[0112] The fused magnesia includes 5% fused magnesia particles with a particle size of >3mm and ≤5mm, 9% fused magnesia particles with a particle size of >1mm and ≤3mm, 9% fused magnesia particles with a particle size of >0mm and ≤1mm, 10% large crystalline fused magnesia particles with a particle size of >3mm and ≤5mm, 17% large crystalline fused magnesia particles with a particle size of >1mm and ≤3mm, 17% large crystalline fused magnesia particles with a particle size of >0mm and ≤1mm, 15% large crystalline fused magnesia fine powder with a particle size of 200 mesh, 6.5% magnesia-alumina spinel with a particle size of 200 mesh, 6% silicon carbide with a particle size of 200 mesh, 3.5% metal aluminum powder with a particle size of 200 mesh, 1% titanium dioxide powder with a particle size of 200 mesh, and 1% boron oxide powder with a particle size of 200 mesh, and 3% phenolic resin binder. In the magnesia-alumina spinel, the MgO content is 32wt%, and the Al2O3 content is 68wt%.

[0113] Embodiment 21

[0114] The unburned magnesia-alumina spinel bricks for the RH refining furnace impregnation tube of this embodiment are prepared by using the same raw materials as those in Example 6, with the following differences: 2% metal aluminum powder, 2.2% titanium dioxide powder, and 1.3% boron oxide powder, i.e., the mass ratio of metal aluminum powder, titanium dioxide powder, and boron oxide powder is 1.5:1.7:1.

[0115] Embodiment 22

[0116] The unburned magnesia-alumina spinel bricks for the RH refining furnace impregnation tubes of this embodiment are prepared by using the same raw materials as those in Example 6, with the following differences: 4.4% metallic aluminum powder, 0.5% titanium dioxide powder, and 0.6% boron oxide powder, i.e., the mass ratio of metallic aluminum powder, titanium dioxide powder, and boron oxide powder is 7.3:0.8:1.

[0117] Embodiment 23

[0118] The unburned magnesia-alumina spinel bricks for the RH refining furnace impregnation tubes of this embodiment are prepared by using the same raw materials as those in Example 6, with the following differences: 1.8% metallic aluminum powder, 2.4% titanium dioxide powder, and 1.3% boron oxide powder, i.e., the mass ratio of metallic aluminum powder, titanium dioxide powder, and boron oxide powder is 1.4:1.8:1.

[0119] Embodiment 24

[0120] The unburned magnesia-alumina spinel bricks for the RH refining furnace immersion tube of this embodiment are prepared by using the same raw materials as those in Example 6, with the following differences: 4.6% metallic aluminum powder, 0.3% titanium dioxide powder, and 0.5% boron oxide powder, that is, the mass ratio of metallic aluminum powder, titanium dioxide powder, and boron oxide powder is 9.2:0.6:1.

[0121] Comparative Example 1

[0122] The unburned magnesia-alumina spinel bricks are used for the RH refining furnace immersion tube of this embodiment. The remaining components in the raw materials for its preparation are the same as those in Example 6, except that titanium dioxide and boron oxide are not added.

[0123] Comparative Example 2

[0124] The RH refining furnace immersion tube of this embodiment uses unburned magnesia-alumina spinel bricks, and the remaining components in the raw materials for its preparation are the same as those in Example 6, except that boron oxide is not added.

[0125] According to the proportions of the above-mentioned embodiments and comparative examples, the raw materials except the binder are configured into a mixture, stirred for 5 minutes, then stirred for another 25 minutes after adding the binder, and formed by a 1600-ton electric screw press. The molding size is 230mm×114mm×75mm, and dried in a drying kiln for 24 hours. The inspection and sampling of bricks are carried out in accordance with GB / T7321. The test was carried out after burning in the laboratory for 1600*3 hours. The test results are shown in Table 1 below. Among them, the slag resistance of magnesium-aluminum spinel bricks is reflected by porosity and high-temperature flexural strength. The lower the porosity, the better the slag resistance, and the higher the high-temperature flexural strength, the better the slag resistance. High temperature resistance is reflected by high-temperature flexural strength. Wear resistance is reflected by high-temperature flexural strength and compressive strength.

[0126] Table 1

[0127] <![CDATA[Volume density after firing / g / cm 3 > Porosity after firing / % Compressive strength after burning / MPa 1400*0.5h high temperature flexural strength / MPa Example 1 3.01 12.3 92 7.3 Example 2 3.01 12.1 95 7.6 Example 3 3.02 11.8 106 8.9 Example 4 3.02 11.5 108 9.0 Example 5 3.02 11.2 114 9.9 Example 6 3.02 11.3 116 10.2 Example 7 3.02 11.3 115 9.7 Example 8 3.02 11.9 103 8.6 Example 9 3.02 11.7 101 8.3 Example 10 3.01 12.0 92 7.2 Embodiment 11 3.02 11.3 115 10 Example 12 3.02 11.3 112 9.8 Example 13 3.02 11.5 108 9.3 Embodiment 14 3.02 11.4 104 9.2 Embodiment 15 3 12.3 91 7.6 Example 16 3 12.0 87 7.5 Embodiment 17 3.02 11.4 112 10 Embodiment 18 3.02 11.4 113 9.8 Embodiment 19 3.01 11.7 98 8.2 Embodiment 20 3.01 11.4 95 8.5 Embodiment 21 3.02 11.3 113 10.1 Embodiment 22 3.02 11.3 110 9.7 Embodiment 23 3.01 11.3 91 7.8 Embodiment 24 3.01 11.3 82 8.2 Comparative Example 1 3 11.4 72 6.2 Comparative Example 2 3 11.5 76 6.9

[0128] It can be seen from the data in Table 1 that the unburned magnesium-aluminum spinel brick for the RH refining furnace dip tube of Comparative Example 1 does not add titanium dioxide and boron oxide, wherein magnesium oxide reacts slowly with aluminum oxide in magnesium-aluminum spinel and cannot be further effectively combined to form magnesium-aluminum spinel. Therefore, the brick has poor comprehensive performance in terms of high temperature resistance, wear resistance and slag resistance. The unburned magnesium-aluminum spinel brick for the RH refining furnace dip tube of Comparative Example 2 does not add boron oxide, and its comprehensive performance is slightly better than that of Comparative Example 1, but still poor. The unburned magnesium-aluminum spinel brick for the RH refining furnace dip tube of each embodiment of the present invention has better comprehensive performance than Comparative Examples 1 and 2.

[0129] In each embodiment of the present invention, in Embodiments 1-10, the mass percentages of each component of the raw materials are different, among which, compared with Embodiments 1, 2, and 10, the mass percentages of each component in Embodiments 3-9 are within a preferred range, and the comprehensive performance is better. Furthermore, compared with Embodiments 3, 4, 8, and 9, the comprehensive performance of the unburned magnesia-alumina spinel bricks in Embodiments 5-7 is better, and the mass percentages of each component are within a further preferred range.

[0130] Compared with Example 6, Examples 11-16 differ in that the mass contents of magnesium oxide and aluminum oxide in the magnesium-aluminum spinel are different. Among them, the mass contents of magnesium oxide and aluminum oxide in Examples 6 and 11-14 are within the preferred range, and the comprehensive performance of the unfired magnesium-aluminum spinel brick is better. The mass contents of magnesium oxide and aluminum oxide in Examples 6, 11, and 12 are in a further preferred range.

[0131] Compared with Example 6, Examples 17-20 differ in that the total mass ratio of fused magnesia and large crystal fused magnesia to magnesia-alumina spinel is different. Among them, the mass ratios in Examples 6, 17, and 18 are all within the preferred range, and the comprehensive performance of unfired magnesia-alumina spinel bricks is better.

[0132] Compared with Example 6, Examples 21-24 differ in that the mass ratios of metal aluminum powder, titanium dioxide powder and boron oxide powder are different. Among them, the mass ratios in Examples 6, 21 and 22 are all within the preferred range, and the comprehensive performance of the unfired magnesia-alumina spinel brick is better.

[0133] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An unburned magnesia-alumina spinel brick for RH refining furnace immersion tube, characterized in that: The raw materials for its preparation include the following components in percentage by mass: 8% to 35% of fused magnesia, 39% to 71% of large crystalline fused magnesia, 8% to 12% of magnesia-aluminum spinel, 5% to 10% of silicon carbide, 1.5% to 4.5% of metal aluminum powder, 0.5% to 2.5% of titanium dioxide powder and 0.3% to 1.8% of boron oxide powder, and 1% to 5% of external binder; the mass ratio of the total mass of fused magnesia and large crystalline fused magnesia to magnesia-aluminum spinel is 7.4 to 10:1; the mass ratio of metal aluminum powder, titanium dioxide powder and boron oxide powder is 1.5 to 8.5:0.8 to 1.7:1; in the magnesia-aluminum spinel, the MgO content is 30wt% to 35wt%, and the Al2O3 content is 65wt% to 70wt%; In fused magnesia, MgO>97.2wt%, SiO2<0.8wt%, Fe2O3<0.6wt%, Al2O3<0.15wt%, CaO<1.5wt%, and loss on ignition<0.1wt%; in large-crystal fused magnesia, MgO>97.5wt%, SiO2<0.8wt%, Fe2O3<0.6wt%, Al2O3<0.15wt%, CaO<1.5wt%, and loss on ignition<0.1wt%.

2. The unburned magnesia-alumina spinel brick for RH refining furnace immersion tube according to claim 1, characterized in that: The raw materials for its preparation include the following components in percentage by mass: Fused magnesia 19%~27%, large crystal fused magnesia 48.3~60.7%, magnesia alumina spinel 8%~11%, silicon carbide 7%~8%, metallic aluminum powder 2%~4.5%, titanium dioxide powder 0.5~2.2% and boron oxide powder 0.5%~1.5%, plus a binder 1%~5%.

3. The unburned magnesia-alumina spinel brick for RH refining furnace immersion tube according to claim 1, characterized in that: In magnesium-aluminum spinel, MgO>32.5wt%, Al2O3>65wt%, Fe2O3<1wt%, SiO2<0.15wt%, CaO<0.5wt%, ignition loss<3.5wt%, bulk density of magnesium-aluminum spinel>3.4g / cm 3 .

4. The unburned magnesia-alumina spinel brick for RH refining furnace immersion tube according to claim 1, characterized in that: The fused magnesia includes fused magnesia particles with a particle size of >3mm and ≤5mm, fused magnesia particles with a particle size of >1mm and ≤3mm, and fused magnesia particles with a particle size of >0mm and ≤1mm; the mass ratio of the fused magnesia particles with a particle size of >3mm and ≤5mm, the fused magnesia particles with a particle size of >1mm and ≤3mm, and the fused magnesia particles with a particle size of >0mm and ≤1mm is 1:1~5:1~4.

5. The unburned magnesia-alumina spinel brick for RH refining furnace immersion tube according to claim 1, characterized in that: The particle size of magnesium aluminum spinel is 200 mesh; The particle size of silicon carbide is 200 mesh; The particle size of the aluminum powder is 200 mesh; The particle size of titanium dioxide powder is 200 mesh; The particle size of the boron oxide powder is 200 mesh.

6. A method for preparing an unburned magnesia-alumina spinel brick for an RH refining furnace immersion tube as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Fused magnesia, large crystal fused magnesia, magnesia-alumina spinel, silicon carbide, metal aluminum powder, titanium dioxide powder and boron oxide powder are mixed, a binder is added and mixed, and the mixed material is molded to obtain the unburned magnesia-alumina spinel brick for the RH refining furnace immersion tube.

Citation Information

Cited By

  • Periclase-high-entropy spinel composite refractory material and preparation method thereof

    CN122010579A